2016
DOI: 10.1590/s1677-5538.ibju.2015.0477
|View full text |Cite
|
Sign up to set email alerts
|

Predictive risk factors of postoperative urinary incontinence following holmium laser enucleation of the prostate during the initial learning period

Abstract: Purpose:To determine the predictive factors for postoperative urinary incontinence (UI) following holmium laser enucleation of the prostate (HoLEP) during the initial learning period.Patients and Methods:We evaluated 127 patients with benign prostatic hyperplasia who underwent HoLEP between January 2011 and December 2013. We recorded clinical variables, including blood loss, serum prostate-specific antigen levels, and the presence or absence of UI. Blood loss was estimated as a decline in postoperative hemoglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…investigated the relationship between PV and the incidence of stress urinary incontinence after HoLEP, and discovered that large prostate size is associated with longer operative time and longer time of manipulation with the sheath across the external sphincter during HoLEP 12 . Other previous reports suggested that the damage to the urethral sphincter as a result of prolonged operation times was one of the causes of postoperative TUI; they emphasized the importance of reducing operation times 13,15,22 . The present results were consistent with their reported findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…investigated the relationship between PV and the incidence of stress urinary incontinence after HoLEP, and discovered that large prostate size is associated with longer operative time and longer time of manipulation with the sheath across the external sphincter during HoLEP 12 . Other previous reports suggested that the damage to the urethral sphincter as a result of prolonged operation times was one of the causes of postoperative TUI; they emphasized the importance of reducing operation times 13,15,22 . The present results were consistent with their reported findings.…”
Section: Discussionsupporting
confidence: 91%
“…Urinary incontinence has a significant impact on daily activities, and many urologists avoid procedures associated with a high incidence of postoperative urinary incontinence. Although certain studies have investigated incontinence after HoLEP, the occurrence of postoperative TUI has been found to vary across studies, reflecting the lack of a standard definition of incontinence 2,15 . Nam et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of SUI following HoLEP has been reported in several studies as 4.9%–12.5% [ 5 - 7 ]. The factors possibly associated with SUI following HoLEP include the surgeon’s experience, the presence of diabetes mellitus, large prostate volume, greater reduction in postoperative prostate-specific antigen levels, longer operation time, longer enucleation time, and increased blood loss [ 5 , 8 - 10 ]. SUI following HoLEP improves spontaneously within 3 months in 70%–90% of patients, and studies of transient SUI usually focus on the 3-month postoperative period [ 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The factors possibly associated with SUI following HoLEP include the surgeon’s experience, the presence of diabetes mellitus, large prostate volume, greater reduction in postoperative prostate-specific antigen levels, longer operation time, longer enucleation time, and increased blood loss [ 5 , 8 - 10 ]. SUI following HoLEP improves spontaneously within 3 months in 70%–90% of patients, and studies of transient SUI usually focus on the 3-month postoperative period [ 5 , 8 ]. Although physicians can counsel patients that SUI will improve within 3 months, this information usually causes significant stress and anxiety for the patient and decreases the patient’s quality of life throughout the duration of SUI.…”
Section: Introductionmentioning
confidence: 99%
“…Stress urinary incontinence is usually caused by the weakness and stretching of the external sphincter due to an enlarged prostate. 16 On some occasions, enucleation of the adenoma proximal to the external sphincter, especially in the 12o'clock region, may cause transient incontinence. 17 This was mostly a short-term complication and resolved effectively after a period of close observation and symptomatic treatment.…”
mentioning
confidence: 99%